Foot anatomy, walking energetics, and the evolution of human bipedalism. Issue 156 (July 2021) - Charles, James P.; Grant, Barbara; D'Août, Kristiaan; Bates, Karl T.
Abstract: Interspecies differences in locomotor efficiency have been extensively researched, but within-species variation in the metabolic cost of walking and its underlying causes have received much less attention. This is somewhat surprising given the importance of walking energetics to natural selection, and the fact that the mechanical efficiency of striding bipedalism in modern humans is thought to be related in some part to the unique morphology of the human foot. Previous studies of human running have linked specific anatomical traits in the foot to variations in locomotor energetics to provide insight into form-function relationships in human evolution. However, such studies are relatively rare, particularly for walking. In this study, relationships between a range of functional musculoskeletal traits in the human lower limb and the energetics of walking over compliant and noncompliant substrates are examined, with particular focus on the lower limb and foot. Twenty-nine young, healthy individuals walked across three surfaces—a noncompliant laboratory floor, and compliant 6 cm and 13 cm thick foams—at self-selected speeds while oxygen consumption was measured, from which the metabolic cost of transport was calculated. Lower limb lengths, calcaneus lengths, foot shape indices, and maximum isometric plantarflexion torques were also measured and subsequently tested for relationships with metabolic cost over these surfaces using linear regression. It was found that metabolic cost varied considerably between individuals within and across substrate types, but this variation was not statistically related to or explained by variations in musculoskeletal parameters considered to be adaptively important to efficient bipedal locomotion. This therefore provides no supportive evidence that variations in these gross anatomical parameters confer significant advantages to the efficiency of walking, and therefore suggest caution in the use of similar metrics to infer differences in walking energetics in closely related fossil species.